2005
DOI: 10.1038/nature03806
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional critical behaviour in a quasi-two-dimensional organic conductor

Abstract: Changing the interactions between particles in an ensemble--by varying the temperature or pressure, for example--can lead to phase transitions whose critical behaviour depends on the collective nature of the many-body system. Despite the diversity of ingredients, which include atoms, molecules, electrons and their spins, the collective behaviour can be grouped into several families (called 'universality classes') represented by canonical spin models. One kind of transition, the Mott transition, occurs when the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
309
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(348 citation statements)
references
References 26 publications
34
309
5
Order By: Relevance
“…In the intermediate region of U ≈ W, a first-order phase boundary, known as a Mott boundary, appears. The conceptual pressure versus temperature phase diagram in which the antiferromagnetic phase is adjacent to the superconducting phase was established by Kanoda et al [4,7,8], which was confirmed precisely by Kagawa et al by gas-pressure controlled experiments [9]. According to the phase diagram, the insulating and metallic/superconducting states are tunable by external or chemical pressures.…”
Section: Electronic Structure and Phase Diagram Of κ-(Bedt-ttf) 2 X Smentioning
confidence: 65%
“…In the intermediate region of U ≈ W, a first-order phase boundary, known as a Mott boundary, appears. The conceptual pressure versus temperature phase diagram in which the antiferromagnetic phase is adjacent to the superconducting phase was established by Kanoda et al [4,7,8], which was confirmed precisely by Kagawa et al by gas-pressure controlled experiments [9]. According to the phase diagram, the insulating and metallic/superconducting states are tunable by external or chemical pressures.…”
Section: Electronic Structure and Phase Diagram Of κ-(Bedt-ttf) 2 X Smentioning
confidence: 65%
“…50 This argument, however, does not hold for κ-CN where no magnetic order is present down to lowest temperatures. Pressure dependent investigations on κ-Cl showed that the bandwidth-controlled Mott criticality involves critical fluctuations in charge, 58 spin, 59 and lattice. 60,61 Nothing like that is known for the spin-liquid compound κ-CN for the intermediate temperature range.…”
Section: Discussionmentioning
confidence: 99%
“…In particular one needs to take care to account for the possible coexistence of metallic and insulating phases; this is expected as the Mott transition is first order in the organic charge-transfer salts. 62,63 The existence of a pseudogap has also been suggested in -͑BEDT-TSF͒ 2 GaCl 4 ͑Ref. 64͒ from microwave conductivity measurements.…”
Section: Open Problems and Future Experimentsmentioning
confidence: 99%